Informality, labour transitions, and the livelihoods of workers in Latin America - Roxana Maurizio; Ana Paula Monsalvo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper studies the incidence and heterogeneity of labour informality in six Latin American countries-Argentina, Brazil, Ecuador, Mexico, Paraguay, and Peru. We divide workers into five work statuses: formal wage-employed, formal self-employed, upper-tier informal wageemployed, lower-tier informal wage-employed, and informal self-employed. We evaluate the patterns of the occupational turnover between these work statuses and assess their impact on wage dynamics. In all the countries, wages are highest for formal workers and lowest for lower-tier informal jobs. The proportion of formal workers who maintain their work status of origin or move up the job ladder is significantly higher than those who transition into lower-paying work statuses. However, despite the high labour turnover experienced by lower-tier informal wage employees, most failed to move up the wage ladder. Education plays an important role, as it increases the probability of transitioning into a better job and, within informality, the chance of better wages.
Keywords: J31; J46; N36; 330; informality; occupational turnover; education; wage dynamics; Latin America